Design of a real-time GSM-Based LPG leakage detector - Amuzuvi, C. K.; Wiredu, C.; Amoah, R. K. (University of Mines and Technology, 2017)
This paper is a follow up to an earlier paper, which reviewed the opportunities and threats of the usage of Liquefied Petroleum Gas in homes and industries in Ghana. In this paper, the design of an electronic gas leakage monitoring system in real-time is proposed, to alert people in homes and industries in Ghana of gas leakages through persistent text messages with accompanying beeps. The importance of using such a system in Ghana is due to the increased spate of fire outbreaks in homes where at least one or more gas cylinders can be found. This is because in a developing country like Ghana, the transportation of cisterns for gas storage to homes and industries is not done through piping. The ubiquitous use of mobile phones in Ghana makes it easier for the use of this system to alert occupants of homes and industries about gas leakages from their cylinders
Keywords: Liquefied Petroleum Gas; Microprocessor; Wireless Communication; Simulation Mode